Inklusion, (k)eine ganz besondere Kunst?! Das Konstrukt "Sonderpädagogische Förderbedarf" (als eine Diagnose) zwischen Schutz und Stigma - Kottmann, Brigitte ("Die Bildung Aller" - Kunstpädagogik und Inklusion)

Rezension des Buches "Schulentwicklung Inklusion. Empirische Einzelfallstudie eines Schulentwicklungsprozesses" von Angelika Bengel - Kottmann, Brigitte (Zeitschrift für Grundschulforschung)

Inklusive Diagnostik in der Schule - Dexel, Timo; Kottmann, Brigitte (Individuelle Förderung - Heterogenität und Handlungsperspektiven in der Schule)

Improper signaling for multicell MIMO RIS-assisted broadcast channels with I/Q imbalance - Soleymani, Mohammad; Santamaria, Ignacio; Schreier, Peter J (IEEE Transactions on Green Communications and Networking)

A GLRT for estimating the number of correlated components in sample-poor mCCA - Hasija, Tanuj; Marrinan, Timothy (Proc. 30th European Signal Processing Conference (EUSIPCO))

Computational Essays as an Approach for Reproducible Data Analysis in lower Secondary School - Hüsing, Sven; Podworny, Susanne (Proceedings of the IASE 2021 Satellite Conference)
Data Science has become an increasingly important aspect of our everyday lives as we gain a lot of different insights from data analyses, for example in the context of environmental issues. In order to make the process of data analyses comprehensible for lower secondary school students, we developed a data analysis project for computer science classes, focusing on gaining insights from environmental data by using the concept of epistemic programming. In this article, we report on the second implementation of this project, which was conducted in a ninth-grade computer science class. Concretely, we want to examine, how far the students were able to create computational essays to conduct reproducible data analyses on their own. In this regard, the computational essays created with the help of the professional tool Jupyter Notebooks will be examined in terms of aspects of reproducibility.

Ebenen des Narrativen in Bildimpulsen und Erzähltexten : Eine empirische Studie über Wirkungspotentiale von Bildern auf schriftliche Erzählfähigkeiten in der Grundschule - Drepper, Laura

Liquid flow morphology investigation in structured packings for offshore applications using a novel flow imaging sensor - Mamedov, Tural; Schleicher, Eckhard; Schubert, Markus; Ehlert, Thomas; Kenig, Eugeny Y.

Die Huixian-Figuren: über materielle und immaterielle Aspekte einer Kunstfälschung - Duschner, Paul (Im-Materiell. Kulturerbe-Studien für Eva-Maria Seng zum 60. Geburtstag)

Man darf die Unterhaltung nicht den Feinden der Unterhaltung überlassen. - Schroeter-Wittke, Harald; Kirsner, Inge (Pandemie im Film. Religiöse und ästhetische Transformationen in der Populärkultur)

Gottesdienst feiern - Schroeter-Wittke, Harald (Handbuch Studierendenseelsorge. Gemeinden – Präsenz an der Hochschule – Perspektiven)

Einleitung - Schroeter-Wittke, Harald; Janus, Richard (Lust und Abgrund. Theologische und kulturwissenschaftliche Zugänge zum Begehren)

Pandemie im Film. Religiöse und ästhetische Transformationen in der Populärkultur

Lust und Abgrund. Theologische und kulturwissenschaftliche Zugänge zum Begehren

Echt jetzt?! Fake und Wirklichkeiten - Schroeter-Wittke, Harald (BRU-Magazin)

Steuerreformen: Investitionsstimulus oder bloß heiße Luft? Wann steuerliche Verlustrückträge der Wirtschaft helfen können - Sureth-Sloane, Caren

Men in skintight pants? Changing body images of masculinity in between contemporary athletic and historically ethnic discourses - Haller, Melanie; Gerlsbeck, Silvia (Carmen Dexl (Ed.): De/Constructing Masculinity?, Palgrave)

Synthesis and Characterization of Catalytically Active Au Core─Pd Shell Nanoparticles Supported on Alumina - Feng, Yanyue; Schaefer, Andreas; Hellman, Anders; Di, Mengqiao; Härelind, Hanna; Bauer, Matthias; Carlsson, Per-Anders (Langmuir)
A two-step seeded-growth method was refined to synthesize Au@Pd core@shell nanoparticles with thin Pd shells, which were then deposited onto alumina to obtain a supported Au@Pd/Al2O3 catalyst active for prototypical CO oxidation. By the strict control of temperature and Pd/Au molar ratio and the use of l-ascorbic acid for making both Au cores and Pd shells, a 1.5 nm Pd layer is formed around the Au core, as evidenced by transmission electron microscopy and energy-dispersive spectroscopy. The core@shell structure and the Pd shell remain intact upon deposition onto alumina and after being used for CO oxidation, as revealed by additional X-ray diffraction and X-ray photoemission spectroscopy before and after the reaction. The Pd shell surface was characterized with in situ infrared (IR) spectroscopy using CO as a chemical probe during CO adsorption–desorption. The IR bands for CO ad-species on the Pd shell suggest that the shell exposes mostly low-index surfaces, likely Pd(111) as the majority facet. Generally, the IR bands are blue-shifted as compared to conventional Pd/alumina catalysts, which may be due to the different support materials for Pd, Au versus Al2O3, and/or less strain of the Pd shell. Frequencies obtained from density functional calculations suggest the latter to be significant. Further, the catalytic CO oxidation ignition-extinction processes were followed by in situ IR, which shows the common CO poisoning and kinetic behavior associated with competitive adsorption of CO and O2 that is typically observed for noble metal catalysts.
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Single-Layer T′ Nickelates: Synthesis of the La and Pr Members and Electronic Properties across the Rare-Earth Series - Wissel, Kerstin; Bernardini, Fabio; Oh, Heesu; Vasala, Sami; Schoch, Roland; Blaschkowski, Björn; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver; Cano, Andrés (Chemistry of Materials)
Understanding high-temperature unconventional superconductivity has become a long-lasting problem in which the cuprates stand as central reference materials. Given this impasse, the recent discovery of superconductivity in analogous nickelate thin films represents a fundamental breakthrough calling for the identification of additional materials in this class. In particular, thermodynamically more robust systems are required to “upgrade” nickelate superconductors from thin films to bulk samples. Here, we contribute in this direction by reporting the synthesis of the new single-layer T′ Pr2NiO3F compound, assessing this synthesis in relation to the only previous T′ nickelate La2NiO3F, and analyzing the electronic properties across the R2NiO3F series (R = La–Lu) via first-principles calculations. We find that these mixed anion systems have a comparatively high degree of stability and their synthesis enables a fine-tuning of their composition as inferred from their characterization. Furthermore, we find that these unprecedented square-planar nickelates hold great promise as prospective superconductors due to their exceptional electronic structure.
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Pseudo‐Octahedral Iron(II) Complexes with Near‐Degenerate Charge Transfer and Ligand Field States at the Franck‐Condon Geometry - Moll, Johannes; Naumann, Robert; Sorge, Lukas; Förster, Christoph; Gessner, Niklas; Burkhardt, Lukas; Ugur, Naz; Nuernberger, Patrick; Seidel, Wolfram; Ramanan, Charusheela; Bauer, Matthias; Heinze, Katja (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry